PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PROPERTI DAN PERUMAHAN DI INDONESIA - Monica Nada Tyastriana; Irma Citrayani; Jombrik (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
The goal of a company in the long term is to optimize its value of the company. This study aims to determine the effect of investment decisions, funding decisions, and dividend policies on company value in property and real estate shares listed on the IDX. The population used in this study are companies listed on the IDX. Sampling method with purposive sampling according to predetermined criteria. The research data is secondary data obtained from the Indonesia Stock Exchange (IDX). Testing the hypothesis in this study using multiple linear regression analysis. The results of this study indicate that investment decisions have a significant positive effect on firm value, funding decisions have no significant effect on firm value, and dividend policy has no significant effect on firm value. This shows that investment decisions affect the level of firm value, while funding decisions and dividend policies do not affect the level of firm value.